Niger : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Performance Criterion and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report, 2003)
This paper assesses Niger's Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and Requests for Waiver of Performance Criterion and for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC). Program implementation remained on track at end-September 2002. All nine performance criteria and benchmarks were observed, except for a small and temporary accumulation of external payments arrears and a slight overshooting of wage bill benchmark of 2 percent. Corrective measures to strengthen debt management and reinforce the control of the wage bill were taken.